Build your own transistor radios : a hobbyist's guide to high-performance and low-powered radio circuits - Quan, Ronald (McGraw-Hill's AccessEngineering., 2013)
Provides a guide to designing and constructing transistor radios, including such topics as choosing components, troubleshooting, and sampling.